Pengembangan Media Video Animasi Pembelajaran Berbantuan Artificial Intelligence dan Canva pada Materi Suhu dan Kalor Kelas VII - Aditya Rahmadi Sutanto; Noer Af’idah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop an innovative learning medium in the form of an animated video assisted by Artificial Intelligence (AI) and Canva for the topic of heat and temperature for seventh-grade students. The research employs the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through media validation sheets and student response questionnaires. Validation results from material experts, media experts, and practitioners showed an average score of 96%, categorized as very valid, while the practicality test involving 31 students achieved 98%, categorized as very practical. The integration of AI technology not only accelerates the media production process but also supports interactive and independent learning aligned with the principles of the Merdeka Curriculum. Based on the research findings, the AI- and Canva-assisted animated video media is considered feasible for use both in classroom and independent learning to enhance students’ motivation and engagement.